2022
DOI: 10.1155/2022/8603625
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Clinical Observation of the Effect of Nasal Breathing on Nonanalgesic and Sedative Gastroscopy

Abstract: This study aimed to investigate the safety, tolerance, and comfort of the subjects in gastroscopy by observing and comparing the effect of gastroscopy under two different breathing modes: nasal breathing and nasal inspiration and oral expiration. A total of 60 subjects who underwent routine gastroscopy in the hospital from January 2021 to June 2021 were selected as the research subjects. According to the willingness of the subjects, they were divided into a nasal breathing group and a nasal inspiration and ora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
1
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%